Performance Analysis of Flywheel Addition on Drive System of Rotary Friction Welding Machine - Yohanes, Yohanes; Siregar, Erikson; Susilawati, Anita; Badri, Muftil (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2018)
Friction welding is a solid-state welding without the use of filler metal by using pressure method where by two workpieces to be connected. It is placed in contact and regulated relative motion in pressure, so that on the contact surface being heat (close to the metal liquid point), which form the metal connection. A friction welding machine in the laboratory of technology production of the University of Riau has some disadvantages, namely the electric motor as a driver head stock stems that are often damaged due to overheating such as excessive during welding. Thus was interfering with the welding process due to damage to the electric motor. Therefore, this paper purpose is carried out the development of friction welding tool by using flywheel. The Flywheel stores energy during high engine speed, and passes it during low engine speeds to produce a steady turn. In this study used three flywheels with a diameter of 250 mm, which each thick of 10 mm, 20 mm and 30 mm. From the test is obtained the value of the average tensile strength on each flywheel that is 522.736 MPa, 510.648 MPa and 531.79 Mpa.